2019
DOI: 10.1242/jeb.200204
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-N exposure alters neurohormone levels in the hemolymph and mRNA abundance of neurohormone receptors and associated downstream factors in the gills ofLitopenaeus vannamei

Abstract: Effects of ammonia-N (0.05, 2, 10 and 20 mg l −1 ) on the neuroendocrine regulation of ammonia transport were investigated in Litopenaeus vannamei. The results showed that corticotrophinreleasing hormone, adrenocorticotropic hormone, dopamine, noradrenaline and 5-hydroxytryptamine concentrations in all ammonia-N groups increased significantly between 3 and 12 h. Cortisol increased significantly between 3 and 24 h. All hormones except crustacean hyperglycemic hormone were reduced to control levels. mRNA abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 74 publications
(79 reference statements)
2
22
0
Order By: Relevance
“…Chang (2005) recorded an increase in hemolymph CHH of Homarus americanus under conditions of acute hypoxia, elevated temperature and altered salinity. Our group also detected a significant increase in CHH concentration of hemolymph in L. vannamei under ammonia-N stress (Si et al, 2019). Therefore, it can be speculated that under salinity and ammonia-N stress, some hormones may participate in ion regulation together with biogenic amines and are associated with ammonia acclimation.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Chang (2005) recorded an increase in hemolymph CHH of Homarus americanus under conditions of acute hypoxia, elevated temperature and altered salinity. Our group also detected a significant increase in CHH concentration of hemolymph in L. vannamei under ammonia-N stress (Si et al, 2019). Therefore, it can be speculated that under salinity and ammonia-N stress, some hormones may participate in ion regulation together with biogenic amines and are associated with ammonia acclimation.…”
Section: Introductionsupporting
confidence: 57%
“…In addition, there have been many studies on the hypothalamicpituitary-interrenal (HPI) axis of fish. Exposure to ammonia-N enhanced the levels of CRH, ACTH and cortisol in Scophthalmus maximus and L. vannamei (Jia et al, 2017;Si et al, 2019). Moreover, it has been reported that cortisol plays a major role in acclimation to hypersalinity in teleost fish (Gonzalez, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…203 Recently, in crustacean, it has also been reported that after perceiving the low salinity and ammonia-N stress in L. vannamei lead to the secretion of CRH, ACTH and stimulate the release of DA, NE and 5-HT through CRH-ACTH-biogenic amine axis. 171,204 Moreover, Liu et al 71 annotated ACTH-related factors in the brain of L. vannamei after eyestalk ablation by transcriptome technology. In short, these findings emphasize the great similarity with CRH-ACTH-induced BA and glucocorticoid release-related events in invertebrates and vertebrates, respectively.…”
Section: Physico-chemical Factorsmentioning
confidence: 99%
“…2). For instance, exposure of L. vannamei to ammonia or low salinity stress results in the secretion of corticotrophin‐releasing hormone (CRH) and adrenocorticotropic hormone (ACTH) into the haemolymph to stimulate the release of biogenic amines, such as DA, NE and 5‐HT (Jia et al, 2016; Si et al, 2019a). Following the release of these biogenic amines, the membrane receptors, such as D 4 receptor (for DA) and 5‐HT 7 receptor (for 5‐HT), then transduce the signals onto haemocytes to modulate the concentrations of cAMP and cGMP, thereby regulating the levels of intracellular PKA and PKC (Zhao et al, 2016; Zhang et al, 2018a).…”
Section: Effects Of Ammonia Stress On Shrimp Physiology and Biochemistrymentioning
confidence: 99%